New Paradigm for Vinasse Use as Fertilizer in Hydroponics - Andrade, Luís Cláudio Lopes [UNESP]; Putti, Fernando Ferrari [UNESP]; Cremasco, Camila Pires [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP] (Springer Nature, 2022)
Sugarcane agroindustry generates a large volume of residues, with the main one being vinasse. Despite its polluting potential, vinasse has great potential to meet crop nutritional demands at different vegetative stages. However, the fertilizer developed from fresh vinasse has not considered the negative effects of its application in crops. Current innovative processes have sought to reuse elements of interest from this raw material, mainly macronutrients, micronutrients, and organic matter, in hydroponic cultivation systems. This study aimed to evaluate the hydroponic cultivation of lettuce, watercress, and chicory using the nutrient film technique and the use of a fertilizer developed from vinasse for their nutrition. We compared the vinasse fertilizer with conventional salts used for vegetable nutrition. Experiments were conducted in a fully randomized design, with two treatments (conventional and vinasse-fertilizer solutions). Nutritional status diagnosis showed synergism between vinasse organic matter and plants. This is because the elements in vinasse were fundamental for plant development and decisive for its good performance in the vinasse solution (VS). Regarding nutrient absorption (e.g. N, K, Mg, Fe, Zn, and B), VS with the addition of Ca, N, and Fe had similar results as those of conventional solution (CS). The hydroponic solution proposed in this study can be applied to reuse vinasse sustainably.
Keywords: Agro-industrial waste; Fertilizer; Plant nutrition; Sugarcane; Vegetable production